The Influence of Electronic Word of Mouth on Labuan Bajo Content and Celebrity Endorser on TikTok Account @tassy.sy on Generation Z's Visiting Interest - Putri Irawan, Ayra Sekar; Intyaswati, Drina; Mahmood, Qasim (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The recovery of the tourism sector in Indonesia, especially Labuan Bajo, can be overcome by utilizing technological developments and social media such as TikTok. Tassy is one of the traveling content creators who often shares traveling content on TikTok. This study aims to determine how much influence electronic word of mouth (variable X1 ) Labuan Bajo content and celebrity endorsers (variable X2 ) on the TikTok @tassy.sy account on visiting interest (variable Y) Generation Z. The theory used in this research is Source Credibility Theory. The research method used is explanatory quantitative. The sample technique uses Purposive Sampling by distributing questionnaires through TikTok. The research population is followers of the TikTok account @tassy.sy and obtained a sample size of 100 results from the Taro Yamane formula. The results of multiple linear regression analysis show that E-WOM and celebrity endorsers each have a positive and significant effect on visiting interest, with the magnitude of the influence of celebrity endorsers (0.827) greater than E-WOM (0.729). Meanwhile, the interaction between E-WOM and celebrity endorsers has a negative effect on interest in visiting, meaning that the knowledge gained through celebrity endorser accounts on TikTok elaborated with E-WOM related to Labuan Bajo does not increase interest in visiting. The coefficient of determination shows that the contribution of E-WOM on Labuan Bajo content and celebrity endorsers on the @tassy.sy TikTok account to visiting interest is 92.3%.